Zaman al-Fi’l al-Māḍī fī Sūrah Yāsīn - Nafi', Abdulloh; Efendi, Nasikul Mustofa (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2024)
Usually, some of us understand the types of times of fi'il with a monotonous understanding. Fi'il madhi is understood only with the meaning of the past, mudhari' with the meaning of the present and future and fi'il amr which is only intended for the future. This understanding is not in accordance with the existing reality because the meaning of the time of the fi'ils was not narrow, such as fi'il madhi which not only means the past, but also present or future or continuous. The author used Al Quran, Surah Yasin, as the object of this research. The aim of this research is to find out what are the various types of times of fi'il madhi in Surah Yasin. The method used in this research was a qualitative-descriptive method. Using this method, the author collected and grouped the data that had been collected. Then, it was analyzed and described the data based on the theories related to this research. The results found that there are 82 fi'il madhi which were not only have the meaning of the past, but also Qarib, Mustaqbal, and Istimrar.